MATHEMATICAL LITERACY SKILLS BY USING REALISTIC MATHEMATICS EDUCATION-BASED WORKSHEETS - Trinanda, Bunga; Sari, Novita; Sukmaningthias, Novika; Simarmata, Ruth Helen (Prima: Jurnal Pendidikan Matematika, 2024)
This research aims to measure students' mathematical literacy skills after using e-worksheets based on the Realistic Mathematics Education (RME) Approach. This research uses a descriptive qualitative approach. Students in class VIII of SMP N 1 Talang Kelapa, each with low, medium, and high literacy skills, were the subjects of this research. The categorization of students is based on the number of mathematical literacy components resulting from student answers on the test. Data was collected through observation, tests, and interviews. The purpose of observation is to measure the implementation of learning through RME, and the test is to measure students' literacy skills. In data analysis, the elements that appear most frequently are communication, mathematization, and the use of symbolic, formal, and technical language operations. Component 1 appears when students write a statement containing information about a problem and representing the results obtained. Component 2 emerges when students create a mathematical model of the problem, and component 7 emerges when students use formal forms that conform to mathematical definitions and rules. The results of learning observations carried out using e-worksheets based on the RME approach show that learning can be said to be of good quality according to the established criteria.